Assessing the Effect of PVP of Various Molecular Weight (MW) in PES-Ag Membranes: Antimicrobial Study Using E.Coli - Basri, Hatijah; Ismail, Ahmad Fauzi; Aziz, Madzlan (Journal of Science and Technology, 2011)
New polymeric silver (Ag) composites were prepared using polyethersulfone (PES) as polymer material, N-Methyl-2-pyrrolidone (NMP) as solvent and polyvinylpyrollidone (PVP) of various molecular weight (MW) as organic fillers. Silver nitrate (AgNO3) was added by various loading in order to impart an antibacterial property to the composites. The miscibility of PES/Ag/fillers composites were characterized using TGA and any changes in chemical bonding were characterized using ATR-FTIR techniques. The XPS results showed high intensity in Eb(Ag3d) range of 378.1-378.5 and 372.2-372.5 for the highest Ag loading with PVP with the highest MW. This phenomenon had altered the hydrophilicity property of composites. In this study, composites have undergone a bacteria rejection test from E.coli suspension and a domestic waste sample. Composites with highest loading of silver and highest MW of PVP (PES-Ag2P360) was observed for significantly high bacteria rejection, log reduction value (LRV~3). Therefore, PES-silver nanocomposites is a potential membrane for bacteria removal, disinfection and maybe effective for overcoming biofouling problems.